Synthesis and Biological Activities of Some Indolyl Substituted Pyrazolines - Kumar, Pankaj; Singh, Payal; Mishra, A.K.; Singh, Jai; Kumar, Ashok (Asian Journal of Chemistry, 2010)
A series of 2-chloroacetyl methylene-3-substituted phenyl- 6-halo/6,8-dihalo substituted quinazolin-4(3H)-ones, 2- hydrazinoacetylmethylene-3-substituted phenyl-6,8-dihalo substituted quinazolin-4(3H)-ones, 5-(2'-acetyl hydrazinomethyl- 3'-substituted phenyl-6-halo/dihalo substituted) quinazolin-1'-yl-4' (3'H)-one-2-substituted phenyl-4-(2''-substituted)- indol-3''-yl-2-pyrazolines have been prepared. The structures of the compounds were established on the basis of elemental analysis and spectral studies. The newly synthesized compounds were evaluated for their antiinflammatory, analgesic, ulcerogenic liabilities and cyclooxygenase II-inhibitory activities. The structures of these compounds have been elucidated by IR, 1H NMR, mass spectroscopy and elemental analysis.